Penggunaan Teknologi Informasi Komunikasi Untuk Pembelajaran Bahasa Anak Usia Dini: THE USING OF COMMUNICATION INFORMATION TECHNOLOGY FOR EARLY CHILDREN LANGUAGE LEARNING - FISNA KHAIRIAH; DELFI ELIZA; ERMA; INDAH PERMATA DARMA (incrementapedia, 2023)
Children integrate with various digital technologies in everyday life and become their users. This study aims to determine the application of communication science technology in early childhood language learning at Perwad Aur Duri Kindergarten in Padang Timur. This research is a qualitative descriptive research with data collection techniques using interview and observation methods. The subjects in this study were children, totaling 3 educators and 52 children. Based on the results of interviews that have been conducted at Perwad Kindergarten the learning process uses communication science technology as a supporting tool in children's language learning. The learning activities carried out by the teacher's language learning display pictures, video words and practice videos as well as words and sounds. Meanwhile, based on observations, some teachers have implemented and practiced information and communication technology tools to make it easier for child participants to find information, especially in language. Based on the conclusions from the research above, it is identified that the application of communication information technology in Perwad Aur Duri Kindergarten in East Padang